(untitled) (Scientific journal of the Fergana State University, 2024)
Phraseology and vocabulary both have a relationship of synonymy, with both having different stylistic affiliations. Phraseological synonyms are two or more phraseological units denoting one concept, belonging to one class, subcategory, or group, and differing semantically or stylistically. Phraseological units are separately formed units of language that serve to figuratively expressive characterize the surrounding reality. Imagery, being one of the most important characteristics of a phraseological unit, is a key factor determining the existence of phraseosynonymous series. Synonymy is a closer relationship between phraseological units than semantic correlation. Phraseological units must belong to the same syntactic type and have the same intension of meaning. Internal form, the motivating imagery of a linguistic unit, is a key factor determining the existence of phraseosynonymous series. The study proves that the synonymous series is a set of words – synonyms, united by a common lexical meaning and related to one part of speech. The other close semantic links are combined for each member of the series. The organizing principle of terminological synonymy is a conceptual metaphor, and the apparatus of using conceptual metaphor models can be a useful tool to understand and analyze phraseological synonyms.